CHALLENGES IN DEVELOPING JUNIOR HIGH SCHOOL STUDENTS' COMPUTATIONAL THINKING SKILLS IN MATHEMATICS THROUGH PROBLEM-BASED LEARNING - Ghifari, Muhammad Tareq; Nurjanah, Nurjanah; Herman, Tatang; Rahmah, Hania (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
This research aims to analyze students' computational thinking abilities in mathematics learning through problem-based learning. A qualitative approach with a case study design was employed. The research was conducted at SMP Negeri 1 Cibinong, Bogor Regency, West Java. The subjects were three ninth-grade students who had studied material on exponents and roots, selected based on the teacher's recommendations. Data were collected through computational thinking tests and interviews. Based on the analysis, it was found that students, despite their teachers implementing problem-based learning, still lacked strong computational thinking skills. The suboptimal implementation of PBL and the students' unfamiliarity with problem-solving contributed to their difficulty in effectively applying computational thinking skills. In conclusion, the use of problem-based learning in mathematics, particularly in the topics of exponents and roots, has not yet enabled students to fully develop computational thinking skills.